2016
DOI: 10.13189/ujer.2016.040307
|View full text |Cite
|
Sign up to set email alerts
|

Views of School Administrators Related to In-service Training Activities

Abstract: The aim of this research is to specify the views of school administrators views related to in-service training activities. In this research, semi-structured interview method, one of the qualitative research methods, has been used. Content analysis has been used in order to analyze the interview data and themes and sub-themes have been constituted. The target population of the research is consisted of 20 school administrators working in the city centre of Eskişehir having joined in-service training activities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…Types of facilities may be time relaxation, easy provision of study leave, lessen work load. Findings are similar to some extent with findings of Gungor and Yildirim (2016) as they found that school administrators arrange in-service training activities for the teachers in the scope of growing their capabilities, occupational development, performance, motivation, increasing awareness and knowledge level. Table 7 shows that range of correlation matrix of variable for this group is from .761 to .568, value of total variance lies at 6.382 and value of Cronbach alpha is .627.…”
Section: Resultssupporting
confidence: 86%
“…Types of facilities may be time relaxation, easy provision of study leave, lessen work load. Findings are similar to some extent with findings of Gungor and Yildirim (2016) as they found that school administrators arrange in-service training activities for the teachers in the scope of growing their capabilities, occupational development, performance, motivation, increasing awareness and knowledge level. Table 7 shows that range of correlation matrix of variable for this group is from .761 to .568, value of total variance lies at 6.382 and value of Cronbach alpha is .627.…”
Section: Resultssupporting
confidence: 86%
“…Bu bağlamda katılımcılar, hizmet içi eğitimin gerekli olduğu, bu uygulamalara istekle katıldıkları ve hizmet içi eğitim uygulamalarının mesleki gelişimlerine katkı sağladığı yönünde görüş belirtmişlerdir. Alanyazındaki bir çok çalışma sonuçları da yönetici ve öğretmenlerin hizmet içi eğitim uygulamalarını gerekli gördükleri (Gönen ve Kocakaya, 2006;Gültekin ve Çubukçu, 2008;Özen, 2006;Seferoğlu, 2004;Şen, 2003), hizmet içi eğitim faaliyetlerine katılımda istekli oldukları ve hizmet içi eğitim faaliyetlerinin mesleki gelişimlerine katkı sağladığı (Güngör ve Yildirim, 2016;Nartgün, 2006;Pepeler, Murat ve Akmençe, 2016) yönündedir.…”
Section: Discussionunclassified